2021
DOI: 10.3390/brainsci11121571
|View full text |Cite
|
Sign up to set email alerts
|

King-Devick Test Performance and Cognitive Dysfunction after Concussion: A Pilot Eye Movement Study

Abstract: (1) Background: The King-Devick (KD) rapid number naming test is sensitive for concussion diagnosis, with increased test time from baseline as the outcome measure. Eye tracking during KD performance in concussed individuals shows an association between inter-saccadic interval (ISI) (the time between saccades) prolongation and prolonged testing time. This pilot study retrospectively assesses the relation between ISI prolongation during KD testing and cognitive performance in persistently-symptomatic individuals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…In short, the KD test is a 1–2-min, rapid number naming test, often used to assist cognitive impairment in multiple sclerosis or after concussion ( Galetta et al, 2015 ; Gold et al, 2021 ). Notably, it also has clinical utility in other conditions such as Parkinson’s disease and AD.…”
Section: Gaze: An Indirect Link To Neural and Cognitive Functionsmentioning
confidence: 99%
“…In short, the KD test is a 1–2-min, rapid number naming test, often used to assist cognitive impairment in multiple sclerosis or after concussion ( Galetta et al, 2015 ; Gold et al, 2021 ). Notably, it also has clinical utility in other conditions such as Parkinson’s disease and AD.…”
Section: Gaze: An Indirect Link To Neural and Cognitive Functionsmentioning
confidence: 99%
“…They reported median ISI in the 300 ms to 400 ms range, number of saccades in a 130-172 range, and average peak velocities of 299.5°/s. Gold et al 65 assessed the relation between ISI prolongation and prolonged K-DT testing with results showing median ISI values of 379 + 199 ms which they contrasted to their previous research showing 235 + 119 ms 60 and 286 + 49 ms, 26 respectively. The Hecimovich et al 31 study with male youth Australian football participants reported mean saccadic measurements of 151 to 168 and 4 to 7 blinks per test Tejani et al 48 study on baseline eye movements and visual contrast acuity noted an average number of saccades per card (over all three K-DT tests) between 56.9 + 14 and 101 + 41.…”
Section: Discussionmentioning
confidence: 91%
“…Average saccade velocity was mentioned in Tad et al 63 study, however, the usefulness of these two metrics needs to be established in the literature. There have been several studies 26,60,64,65 that have utilized the rapid number naming component of the K-DT with other eye tracking units. The results reported in these studies, such as the number of saccades and ISI, are similar to ones reported in the current study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations